Decolonizing Education or Accepting the Challenge of Taking a Different Path - Solano-Alpízar, José (2015)
This paper discusses the importance of decolonizing education as one of the strategies to help create a new, more human, more caring and more critical vision of the world.  It directs the reader’s attention to a territory of which much has been written –education– but still has many pending discussions regarding the possibility of thinking about another type of education: a type of education that allows us to see ourselves as historical subjects that give meaning to our existence by breaking the ideological attachment to the epistemic, cultural, axiological and ontological frameworks that were used and are still being used to base the current matrix of neocolonial domination.